An extremely chemical and mechanically durable siloxane bearing copolymer coating with self-crosslinkable and anti-icing properties. (15th August 2020) - Wu, Yuan-long; She, Wei; Shi, Dean; Jiang, Tao; Hao, Tong-hui; Liu, Jie; Zhang, Qun-chao; You, Jun; Li, RobertK.Y.
Abstract: Efficient anti-icing techniques are of great implications in many fields of our society. In this work, multi-functional copolymers containing siloxane units are designed to prepare durable anti-icing coating. The presence of siloxane groups endows the copolymers with triggered self-crosslinking ability, strong self-adhesiveness and high structural stability in severe conditions, which further enhanced the mechanical/chemical durability of the composite coatings. The optimal composite coating containing 40 wt% copolymer and 60 wt% fluorinated silicon dioxide exhibits excellent water repellency with contact angle beyond 160° and sliding angle below 2°. The water-freezing time can be postponed to 1765 s at −20 °C in concrete with the ice adhesion strength as low as 68.1 kPa. More impressively, the performance of this anti-icing coating can be well maintained even after over 110 cycles sandpaper abrasion at 2.5 kPa and 20 icing/deicing cycles, or immerging in various corrosive/organic conditions for more than 10 days. The composite coatings can be well applied on surfaces with diverse properties, such as metal, ceramics, glass and polymer for a myriad of anti-icing applications. Graphical abstract: Image 1 Highlights: Fluorinated silicon-based copolymer with self-crosslinking ability was designed. Superhydrophobic coating was prepared by spraying copolymer/F–SiO2 nanocomposites. Remarkable mechanical/chemical robustness and liquid-repellence property were achieved. Durable anti-icing performance was endowed to various materials by depositing the nanocomposites on the surfaces.